2001
DOI: 10.1107/s0909049500017696
|View full text |Cite
|
Sign up to set email alerts
|

HF-STEX and RASSCF calculations on nitrogen K-shell X-ray absorption of purine base and its derivative

Abstract: The nitrogen K-shell X-ray absorption spectra of the purine bases present in nucleic acids, adenine and guanine, were analyzed by using ab initio Hartree-Fock static exchange and restrictedactive-space self-consistent-field calculations. A variety of derivative molecules were calculated to investigate the energetic shifts due to environmental effects on the nitrogen atoms. Shake-up excitations were also addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 3 publications
(12 reference statements)
2
22
0
Order By: Relevance
“…When the N @ -K sites locate in the hexagon ring of the tautomer, such as ade n9 and ade n7, the chemical environment in energy term seems more similar as the three imino N-K peaks are closely positioned. When the N @ -K sites locate in the pentagon ring of the tautomer, such as ade n1 and ade n3, the N-K sites in the hexagon ring, N (7) and N (9) , exhibit similar energy environment. In summary, the adenine tautomers are apparently different in their inner-shell N-K spectra.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When the N @ -K sites locate in the hexagon ring of the tautomer, such as ade n9 and ade n7, the chemical environment in energy term seems more similar as the three imino N-K peaks are closely positioned. When the N @ -K sites locate in the pentagon ring of the tautomer, such as ade n1 and ade n3, the N-K sites in the hexagon ring, N (7) and N (9) , exhibit similar energy environment. In summary, the adenine tautomers are apparently different in their inner-shell N-K spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Molecules of biological relevance often are thermally labile and hardly be brought into the gas phase by sample heating, and for most of DNA bases the spectra of different tautomers superimpose and make the spectra congested [5,6]. As a result, the study of DNA base tautomers has been largely based on computational methods [7,8,9,10,11,12,13]. Most of structural studies with respect to tautomerism of DNA bases, however, has concerned on the valence space [6,7,9,11,12,14,15], which hardly provides a thorough understanding of the role of possible proton transfer reactions without the recognition of inner-shell re-configuration process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accurate prediction of electron spectra, particularly for core shell, is still largely for small molecules. A simple mean for the IPs was employed using the B3LYP and RHF orbital energies without any rigorous scientific basis in a spectral analysis of L-alanine (Mochzuki et al, 2001). In the most recent photoabsorption spectra of small amino acids in gas phase (Plekan et al, 2006), the observed results were semi-empirically assigned for the core ionization potentials (IPs) by subtracting the number of 2.6 eV from the DFT calculated core energies.…”
Section: Introductionmentioning
confidence: 99%